UTILIZING A CASE STUDY APPROACH TO FOSTER CRITICAL THINKING IN FOREIGN LANGUAGE TEACHING FOR MASTERS IN POWER ENGINEERING - Nykyporets, Svitlana (Collection of scientific papers «ΛΌГOΣ», 2023)
This article investigates the effectiveness of a case study approach for the development of critical thinking in foreign language teaching of masters in power engineering. The study revealed that students participating in the case study-based foreign language course exhibited noteworthy enhancements in critical thinking skills. The study also found that the case study-based course was particularly effective in helping students to develop their ability to analyse problems. The case study-based course that was developed in this study helped students to develop their ability to analyse problems, identify relevant information, and generate creative solutions. The results suggest that case studies can be an effective way to help students to develop their critical thinking skills in the context of foreign language learning.